P = 2L + 2W (Starting equation. I'm using caps so L is not confused with 1)

P-2L = 2L - 2L + 2W (subtract 2L from both sides, note that the 2L terms on the right cancel each other. We choose to subtract 2L for just that reason: So the term on the right disappears.)

P - 2L = 2W (same as above)

(P - 2L)/2 = 2W/2 (divide both sides by 2)

P/2 - L(2/2) = W(2/2) (divide out on the left, consolidate the 2s on the right. Recognize that 2/2=1 and we can eliminate that multiplier.)

P/2 - L = W (here is the equation solved for W)

P-2L = 2L - 2L + 2W (subtract 2L from both sides, note that the 2L terms on the right cancel each other. We choose to subtract 2L for just that reason: So the term on the right disappears.)

P - 2L = 2W (same as above)

(P - 2L)/2 = 2W/2 (divide both sides by 2)

P/2 - L(2/2) = W(2/2) (divide out on the left, consolidate the 2s on the right. Recognize that 2/2=1 and we can eliminate that multiplier.)

P/2 - L = W (here is the equation solved for W)